Problems of Speaking English Among Undergraduates : An Investigation Among First Year Faculty of Islamic Studies and Arabic Language (Fia) Students of the South Eastern University of Sri Lanka - M.R Rishad Muhammed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Speaking in second or foreign language has often viewed as the most demand-ing of the four skills. But, most of the ESL learners consider it as a difficult skill to be mastered. Therefore, this study attempted to investigate the problems of speaking English faced by first year FIA students of the SEUSL. Objective of this study was to identify the main problems. Sixty samples were selected from first year FIA students using random sampling technique. Mixed method re-search design was employed in this study. Questionnaire was administrated among sixty students to collect quantitative data and the qualitative data was col-lected through a focused-group interview with six selected students from the samples. Quantitative data was analyzed using SPSS and qualitative data was recorded and transcribed. The findings of this study revealed that students have different kinds of prob-lem in speaking English, like, getting nervous, feeling fear of making mistakes, lack confidence, difficulty in choosing words appropriately and feeling shy. The main factors that caused those problems were reported as lack of confidence, lack of vocabulary, fear of making mistakes and poor listening skill. The stu-dents expect their lecturers to provide more collaborative works, conduct some exciting games and use mother tongue where it is necessary to give instructions to enhance their oral proficiency.